“Kasih Kristus Adalah Dasar Hubungan Suami Dan Isteri”, Menurut Efesus 5:22-33 Dan Implikasinya Bagi Jemaat GMIM Baitani Minanga Wilayah Belang. - Ponggohong , Feibilia Olivia (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2020)
The love of Christ is a Base of husband and wife relationship according to Ephesians 5:22-33 along with the implication in GMIM Baitani Minanga. This Research uses Historicaly Critical Methods to digest the text, Observation, and interview to find out the fact in the Field. The result of this research which suggest the Husband and Wife love and honor each other and the Presbyter have to founding the church by giving a instruction in class of catechism, Pastoral Care for merried couple so that they realize How important to lived as husband and wife according to the love of Christ.